In vivo antimicrobial activity of engineered mesoporous silica nanoparticles targeting intracellular mycobacteria - John Jairo Aguilera-Correa; Yara Tasrini; Miguel Gisbert-Garzarán; Aude Boulay; Tamara Carvalho; Fabien P. Blanchet; María Vallet-Regí; Laurent Kremer (Nature Communications)
Abstract Treatments of Mycobacterium marinum, a common non-tuberculous mycobacterium associated with cutaneous infections are very challenging, emphasizing the development of new therapeutic approaches. Here we report the functionalization of mesoporous silica nanoparticles (MSN) with a series of triphenylphosphonium (TPP) substituents, which endowed them with affinity towards the surface of M. marinum in vitro, as well as within infected THP-1 cells. The presence of these nanoparticles at the bacterial surface prevents their uptake by human macrophages and dendritic cells. When loaded with doxycycline, the nanosystem exerts a potent anti-bacterial effect in planktonic cultures, biofilms, and in M. marinum-infected macrophages. Strikingly, in the M. marinum/zebrafish infection model, the doxycycline-loaded nanoparticles are associated with a pronounced decrease in the bacterial burden and a high embryo survival rate. These results disclose the proposed MSN nanosystems as a promising alternative for the treatment of M. marinum infection and, presumably, against a broader range of mycobacterial infections.